Topological Supercavity Resonances in the Finite System - Lujun Huang; Bin Jia; Yan Kei Chiang; Sibo Huang; Chen Shen; Fu Deng; Tianzhi Yang; David A Powell; Yong Li; Andrey E Miroshnichenko (Advanced Science, 2022)
Abstract Acoustic resonant cavities play a vital role in modern acoustical systems. The ultrahigh quality‐factor resonances are highly desired for some applications such as high‐resolution acoustic sensors and acoustic lasers. Here, a class of supercavity resonances is theoretically proposed and experimentally demonstrated in a coupled acoustic resonator system, arising from the merged bound states in the continuum (BICs) in geometry space. Their topological origin is demonstrated by explicitly calculating their topological charges before and after BIC merging, accompanied by charges annihilation. Compared with other types of BICs, they are robust to the perturbation brought by fabrication imperfection. Moreover, it is found that such supercavity modes can be linked with the Friedrich–Wintgen BICs supported by an entire rectangular (cuboid) resonator sandwiched between two rectangular (or circular) waveguides and thus more supercavity modes are constructed. Then, these coupled resonators are fabricated and such a unique phenomenon—moving, merging, and vanishing of BICs—is experimentally confirmed by measuring their reflection spectra, which show good agreement with the numerical simulation and theoretical prediction of mode evolution. The results may find exciting applications in acoustic and photonics, such as enhanced acoustic emission, filtering, and sensing.